Pais na creche: construindo relações no diálogo cotidiano - Santos, Liliana Santoro (2007)
This Work investigates the relations between the day-care center and the family on daily routine of an Infant Educational Center Jardim Três Marias , in the city of São Paulo, and the importance of a dialogue to stablish this relation. Between some boarded points, they are considered important: the historical survey of the sprouting of the daycare centers in Brazil with emphasis in the city of São Paulo; the history of fight and mobilization of the searched day-care center; the identification of the models that remain until the current days; the inequality in the relation day-care center-family; the importance of the participation of the parents; the representations of the identity of the day-care center. The empirical research investigates what parents and educators think on the daily work of the day-care center, having as focus the routine, the relation daycare center-family, the participation of the parents and the perception of what is a work of quality in the infantile education in the conception of parents and teachers. The collection and the analysis of the data, supported in a bibliographical revision, point two representations that still remain until our days: the family as reference of an idealized model; the day-care center as a standardized model of work having as base the routine disciplining times, spaces and people. Although the conflicts between the adults, of the inequality in the relation between educators and parents, and of other difficulties, to confide for a daily dialogue can be a way for the day-care center to search for the citizen of its action and intentions optimum: the child